The effect of audiovisual feedback of monitor/defibrillators on percentage of appropriate compression depth and rate during cardiopulmonary resuscitation - Hannah Lee; Jay Kim; Somin Joo; Sang-Hoon Na; Sangmin Lee; Sang-Bae Ko; Jinwoo Lee; Seung-Young Oh; Eun Jin Ha; Ho Geol Ryu (BMC Anesthesiology, 2023)
Abstract Background High quality cardiopulmonary resuscitation (CPR) is one of the key elements of the survival chain in cardiac arrest. Audiovisual feedback of chest compressions have been suggested to be beneficial by increasing the quality of CPR in the simulated cardiac arrests. Methods A prospective before and after study was performed to investigate the effect of a real-time audiovisual feedback system on CPR quality during in-hospital cardiac arrest in intensive care units from November 2018 to February 2022. In the feedback period, CPR was performed with the aid of the real-time audiovisual feedback system. The primary outcome was the percentage of compressions with both adequate depth (5.0–6.0 cm) and rate (100–120/minute). Results A total of 27,295 compressions in 30 cardiac arrests in the no-feedback period and 27,965 compressions in 30 arrests in the feedback period were analyzed. The percentage of compressions with both adequate depth and rate was 11.8% in the feedback period and 16.8% in the no-feedback period (P < 0.01). The percentage of compressions with adequate rate in the feedback period was lower than that in the no-feedback period (67.3% vs. 75.5%, P < 0.01). The percentage of beyond-target depth with the feedback was significantly higher than that without feedback (64.2% vs. 51.4%, P < 0.01). Conclusion Real-time audiovisual feedback system did not increase CPR quality and was associated with a higher percentage of compression depth deeper than the recommended 5.0–6.0 cm. It is essential to explore more effective ways of implementing feedback in real clinical settings to improve of the quality of CPR. Trial registration NCT03902873 (study start: Nov. 2018, initial release April 2019, retrospectively registered).